Ownership and Tax Planning in Manufacturing Companies Towards Sustainable Economic Governance (SDG 16) - Rahmawati Juliati; Rahmawati Rahmawati; Sri Hartoko; Eko Arief Sudaryono (Journal of Current Studies in SDGs, 2027)
Objective: To examine the influence of ownership structure on tax planning practices in manufacturing companies listed on the Indonesia Stock Exchange. Specifically, this study investigates the effect of family ownership, foreign ownership, and public ownership on corporate tax planning behavior within the framework of sustainable corporate governance aligned with Sustainable Development Goal (SDG) 16. Method: The research employed a quantitative approach using secondary data obtained from financial reports of manufacturing companies listed on the Indonesia Stock Exchange during 2017–2019. The sample was selected using purposive sampling criteria, resulting in 199 firm-year observations. Multiple linear regression analysis was conducted to examine the relationship between ownership structure and tax planning. Tax planning was measured using the Effective Tax Rate (ETR), while ownership variables were measured based on share ownership proportions.  Results:  The findings indicate that ownership structure significantly influences corporate tax planning. Family ownership, foreign ownership, and public ownership negatively affect ETR, indicating that higher ownership concentration is associated with greater tax planning activities. These results suggest that ownership composition plays an important role in determining corporate tax policies and managerial decisions.  Novelty: Contributing to the literature by examining different ownership types simultaneously and explaining their role in corporate tax planning behavior among Indonesian manufacturing companies. The findings provide insights into how ownership governance mechanisms can support responsible corporate decision-making and strengthen institutional accountability in line with SDG 16.